2016
DOI: 10.1016/j.apcatb.2016.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative power of aqueous non-irradiated TiO 2 -H 2 O 2 suspensions: Methylene blue degradation and the role of reactive oxygen species

Abstract: I am indebted to Håvard J. Haugen, Janne Elin Reseland and Ståle Petter Lyngstadaas. I would like to thank you for the inspirational discussions, progress meetings and the encouragement to present my research outside the department. But most importantly, you backed me up when I needed it the most. You have my respect. I never thought that microbiology is fun. That was before I met Jessica Lönn-Stensrud. Thank you for showing me bakterienes forunderlige verden and for being an excellent supervisor. Thanks, Hann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 242 publications
4
35
0
Order By: Relevance
“…TiO2 nanoparticles did not show intrinsic antibacterial properties ( Figure 3B), and hence, the delay in tRLUmax/2 is suggested to be due to the interaction between TiO2 and H2O2. The non-photocatalytic formation of oxygen centred radicals, due to the interaction of H2O2 and TiO2, has previously been shown (Fenoglio et al 2009;Sanchez et al 2013;Wiedmer et al 2016). These studies suggested that TiO2 can act as a Fenton catalyst and decompose H2O2 into oxygen centred radicals namely superoxide (O2 -• ) and hydroxyl radicals ( • OH).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…TiO2 nanoparticles did not show intrinsic antibacterial properties ( Figure 3B), and hence, the delay in tRLUmax/2 is suggested to be due to the interaction between TiO2 and H2O2. The non-photocatalytic formation of oxygen centred radicals, due to the interaction of H2O2 and TiO2, has previously been shown (Fenoglio et al 2009;Sanchez et al 2013;Wiedmer et al 2016). These studies suggested that TiO2 can act as a Fenton catalyst and decompose H2O2 into oxygen centred radicals namely superoxide (O2 -• ) and hydroxyl radicals ( • OH).…”
Section: Discussionmentioning
confidence: 97%
“…One explanation for the relatively small increase in antibacterial activity may be the nature and location of the radicals formed at the H2O2-TiO2 interface. Earlier results indicated that primarily superoxide radicals (O2 -• ) are formed at this interface and the oxidative effect is limited to the proximity of the surface (Wiedmer et al 2016). Extracellular polymeric matrix (EPS) may protect bacteria from direct contact with TiO2 nanoparticles and thereby hamper the antibacterial effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations